role for T cell-derived interleukin 22 in psoriatic skin inflammation - Boniface, K; Guignouard, E; Pedretti, N; Garcia, M; Delwail, A; Bernard, F.-X; Nau, F; Guillet, G; Dagregorio, G; Yssel, H; Lecron, J.-C; Morel, F (Clinical and experimental immunology, 2007)
Interleukin (IL)-22 is a T cell-derived cytokine that has been reported recently to induce cutaneous inflammation in an experimental murine model of psoriasis, and to induce in vitro an inflammatory-like phenotype. In the present study, we assessed the presence of IL-22 and the IL-22 receptor 1 (IL-22R1) in skin lesions, skin-derived T cells, as well as IL-22 levels in sera from patients with psoriasis. IL-22R1 and IL-10R2 transcripts are expressed at a similar level in psoriatic and healthy skin. In contrast, IL-22 mRNA expression was up-regulated in psoriatic skin lesions compared to normal skin, whereas IL-22 mRNA levels in peripheral blood mononuclear cells from psoriatic patients and normal subjects were similar. Circulating IL-22 levels were significantly higher in psoriatic patients than in normal subjects. T cells isolated from psoriatic skin produced higher levels of IL-22 in comparison to peripheral T cells isolated from the same patients. IL-10 was expressed at similar levels in skin biopsies and peripheral blood mononuclear cells of psoriatic patients and normal subjects. Finally, we show here that supernatants of lesional psoriatic skin-infiltrating T cells induce an inflammatory response by normal human epidermal keratinocytes, resembling that observed in psoriatic lesions. Taken together, the results reported in this study indicate that IL-22 is a cytokine produced by skin-infiltrating lymphocytes that is potentially involved in initiation and/or maintenance of the pathogenesis of psoriasis.